Serum microRNAs in sporadic amyotrophic lateral sclerosis - Freischmidt, Axel; Müller, Kathrin; Zondler, Lisa; Weydt, Patrick; Mayer, Benjamin; Arnim, Christine von; Hübers, Annemarie; Dorst, Johannes; Otto, Markus; Holzmann, Karlheinz; Ludolph, Albert C.; Danzer, Karin M.; et al. (Neurobiology of aging, 2015)
MicroRNAs (miRNAs) are post-transcriptional regulators of gene expression and specific mircoRNA “fingerprints” are thought to contribute to and/or reflect certain disease conditions. Recently, we identified surprisingly homogeneous signatures of circulating miRNAs in the serum of familial amyotrophic lateral sclerosis (ALS) patients, which were already present in presymptomatic carriers of ALS gene mutations. Here, we characterize circulating miRNAs in the serum of sporadic ALS patients. We show that, in contrast to familial ALS, miRNA signatures of sporadic ALS are highly heterogeneous suggesting a number of different etiologies. Nevertheless, 2 miRNAs, miR-1234-3p and miR-1825, could be identified to be consistently downregulated in sporadic ALS. Bioinformatic analysis revealed miRNA fingerprints resembling those of familial ALS patients and mutation carriers in 61% of sporadic ALS patients, while the remaining subgroup had clearly different miRNA signatures. These data support a higher than expected contribution of genetic factors also to sporadic ALS. Moreover, our results indicate a more heterogeneous molecular etiology of sporadic ALS compared with (mono)genic cases, which should be considered for the development of disease modifying treatments.